Peran Pendidikan Pondok Pesantren Dalam Meningkatkan Kedisiplinan Santri di Pondok Pesantren Miftahul Huda Bekasi - Maturidi Maturidi (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2020)
The purpose of this study was to find out how the role of Islamic boarding schools in shaping the character of their students. In this study, the author uses data collection techniques through case studies with purposive interview methods and field observations, thus this research is in the form of qualitative which is supported by books, magazines, and other sources as references that are used in order to solve the problem. The results of the study can be concluded that the role of the Miftahul Huda Islamic Boarding School with all aspects, elements and activities carried out routinely and continuously with supervision carried out 24 hours is very large and significant in shaping the character of students.